Interaction of deuterium plasma with sputter-deposited tungsten nitride films. (25th November 2015) - Gao, L.; Jacob, W.; Meisl, G.; Schwarz-Selinger, T.; Höschen, T.; von Toussaint, U.; Dürbeck, T.
Abstract: Magnetron-sputtered tungsten nitride (WN x ) films were used as a model system to study the behaviour of re-deposited WN x layers which could form in fusion devices with tungsten (W) wall during nitrogen seeding. The interaction of such WN x layers with deuterium (D) plasmas was investigated in dedicated laboratory experiments. D retention and N removal due to D plasma exposure (D flux: 9.9  ×  10 19 D m −2 s −1, ion energy 215 eV) at different temperatures were measured with ion beam analysis (IBA). Low-energy argon sputtering followed by IBA was applied to resolve the D distribution in the top-most surface of WN x with significantly improved depth resolution compared with the standard D depth profiling method by nuclear reaction analysis. Experimentally determined thicknesses for the penetration of D in WN x were compared with the penetration depth for D calculated in SDTrimSP simulations. Results show that D is only retained within the ion penetration range for samples exposed at 300 K. In contrast to the 300 K case, D diffuses beyond the implantation depth in a sample exposed at 600 K. However, the D penetration depth is much lower than in pure W at comparable conditions. The total amount of retained D in WN x at 600 K is by 50% lower than for implantation at 300 K with the same D fluence. Nitrogen is removed only within the D ion range.